Clinical outcome after endoscopic submucosal dissection for early gastric cancer of absolute and expanded indication. Issue 17 (April 2017) - Kim, Ju Seok; Kang, Sun Hyung; Moon, Hee Seok; Lee, Eaum Seok; Kim, Seok Hyun; Sung, Jae Kyu; Lee, Byung Seok; Jeong, Hyun Yong
Abstract : Abstract: This study evaluated the clinical outcome of endoscopic submucosal dissection (ESD) in minute submucosa (SM) invasion or undifferentiated early gastric cancer (EGC) and analyzed factors related to local recurrence after ESD. We retrospectively reviewed the chart of EGC patients, who underwent ESD at our tertiary hospital between January 2009 and 2015. The patients' characteristics and clinical outcomes were compared among an absolute indication, minute SM invasion, and undifferentiated EGC group. Of 885 total patients, 729 composed the absolute indication group; 65, the differentiated, SM invasion group; and 51, the undifferentiated, confined mucosa group. Follow-up was conducted for average (± standard deviation) 34.12 (± 10.6) months; as compared to the absolute indication group, both en bloc resection and curative resection rate were low in the other 2 groups, but there were no significant differences in procedure-related complication, local recurrence, and survival rate. Comparing the cases of ESD performed at our hospital from 2005 to 2009 with those performed between 2009 and 2015, en bloc resection (80.5% vs 89.1%, P  = .001) and curative resection rate (86.2% vs 92.1%, P  = .011) were higher in the latter study. Noncurative resection and tumor size of more than 2 cm were factors associated with local recurrence. ESD in minute SM invasion or undifferentiated EGC showed an unfavorable short-term outcome as compared to that in the absolute indication group, but there were no differences in local recurrence and overall survival rate. Therefore, in minute SM invasion or undifferentiated EGC patients, ESD could be recommended as a therapeutic option.